History of Areal Collection and Research of Bukhara Folklore - qizi, Urinova Maftuna Numon (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the history of the study of Bukhara folklore and the method of area research. The Bukhara oasis, with its rich cultural heritage, makes a worthy contribution to the treasury of Uzbek folklore. Therefore, their study began much earlier. The services of Abdurauf Fitrat, H. Zarif, G. Yunusov, T. Mirzayev deserve recognition. The article provides detailed information about the folklorist Akhunjon Safarov, who led the collection, study and publication of Bukhara folklore. His songs “Karakullik kuychilar”, “Shirinqishloq latifalari”, “To‘y muborak, yor-yor”, “Bo‘zlardan uchgan g‘azal-ay”, “El suyarim alla”, “Alla-yo alla” to It was noted that the plots were analyzed and formed on the basis of the areal survey method.